Comparison of magnetic island stabilization strategies from magneto-hydrodynamic simulations. (17th February 2017) - Février, O; Maget, P; Lütjens, H; Beyer, P
Abstract: The degradation of plasma confinement in tokamaks caused by magnetic islands motivates to better understand their possible suppression using electron cyclotron current drive (ECCD) and to investigate the various strategies relevant for this purpose. In this work, we evaluate the efficiency of several control methods through nonlinear simulations of this process with the toroidal magneto-hydro-dynamic (MHD) code XTOR-2F (Lütjens and Luciani 2010 J. Comput. Phys. 229 8130–43 ), which has been extended to incorporate in Ohm's law a source term modeling the driven current resulting from the interaction of the EC waves with the plasma. A basic control system has been implemented in the code, allowing testing of advanced strategies that require feedback on island position or phase. We focus in particular on the robustness of the control strategies towards uncertainties that apply to the control and ECCD systems, such as the risk of misalignment of the current deposition or the possible inability to generate narrow current deposition.